“3D Cladistics”: a new perspective for phylogenetic analyses and a tool for citizen science - Márcia Venâncio; Carlos Antunes; Dimítri de Araújo Costa (Academia Biology)
This study uses the cladistics method, three-dimensional (3D) illustration, and its importance for scientific communication in referring to phylogeny study. Since morphological cladistics presently is less used, we intend to innovate this analysis, so it becomes more perceptible visually, which may awaken interest in phylogenetic studies. We analyzed echinoderm genera Marthasterias (main analysis group) and Asterias (outgroup), and we did a 3D model of the organisms and their characteristics and the cladogram. As this study is based on morphological cladistic analysis, it has limitations concerning the data compilation, comparison, and synthesis. Nevertheless, it gives a wider view of the characters analyzed. This kind of visual communication is important to capture the attention of the general public, being an appealing way of communicating, allowing to improve science literacy. In the future, the 3D interactive graphics based on the cladistic analysis of the characters can be applied in museums, books, websites, and beyond.